2001
DOI: 10.1164/ajrccm.164.8.2101100
|View full text |Cite
|
Sign up to set email alerts
|

Female Gender Exacerbates Respiratory Depression in Leptin-deficient Obesity

Abstract: Obese females are less predisposed to sleep-disordered breathing and have higher serum leptin levels than males of comparable body weight. Because leptin is a powerful respiratory stimulant, especially during sleep, we hypothesized that the elevated leptin level is necessary to maintain normal ventilatory control in obese females. We examined ventilatory control during sleep and wakefulness in male and female leptin-deficient obese C57BL/6J-Lep(ob) mice, wild-type C57BL/6J mice with dietary-induced obesity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 28 publications
5
41
2
2
Order By: Relevance
“…We did not study other characteristics of obesity, but obesity is a state of sufficient magnitude to produce adverse health consequences, such as type 2 diabetes and hypertension. We do not know why only females have a higher body weight; however, there are many differences between the sexes that can affect obesity; it has been reported that sex hormones influence obesity (40), that the association between body mass index and lipids͞lipoproteins is stronger in females than in males (41), and that leptin-deficient obesity is affected by female sex (42). The finding that mice generated by culture in FCS or by micromanipulation (nuclear transfer) are susceptible to obesity (43,44) is consistent with a supposed phenotypic influence by preimplantation in vitro procedures.…”
Section: Discussionmentioning
confidence: 99%
“…We did not study other characteristics of obesity, but obesity is a state of sufficient magnitude to produce adverse health consequences, such as type 2 diabetes and hypertension. We do not know why only females have a higher body weight; however, there are many differences between the sexes that can affect obesity; it has been reported that sex hormones influence obesity (40), that the association between body mass index and lipids͞lipoproteins is stronger in females than in males (41), and that leptin-deficient obesity is affected by female sex (42). The finding that mice generated by culture in FCS or by micromanipulation (nuclear transfer) are susceptible to obesity (43,44) is consistent with a supposed phenotypic influence by preimplantation in vitro procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators have demonstrated that obesity can also impose structural loads on the airway (5) that elevate pharyngeal collapsibility in the fa/fa rat and that serotonergic mechanisms can offset this mechanical effect (27). We have demonstrated that a similar defect in leptin signaling in obese ob/ob mice accounts for the development of the obesity-hypoventilation syndrome in a murine model (29,38), suggesting that mouse strains may ultimately serve to probe the genetic determinants of sleeprelated breathing disorders. Nevertheless, a mouse model of upper airway function will be required to explore the genetic control of pharyngeal collapsibility.…”
mentioning
confidence: 88%
“…These mice exhibit abnormal patterns of breathing with elevated levels of carbon dioxide. Importantly, the ventilatory response of these mice to carbon dioxide is reduced in both wakefulness and non-REM sleep compared with that of wild-type mouse controls, and is absent during REM sleep [46,47]. In addition, it appears that absence of leptin also produces marked alterations in the mechanical properties of the lung, including reduced total lung capacity and lung compliance [48].…”
Section: Neurohormonal and Neuromodulators Of Breathingmentioning
confidence: 98%
“…Most obese individuals do not hypoventilate, and therefore it has been speculated that these increasing leptin levels may help to maintain alveolar ventilation in the face of the increased ventilatory load caused by obesity [49]. If this compensatory mechanism were lost, for instance with the development of leptin resistance [49,50], then awake hypercapnia could emerge [47,51]. Leptin resistance is recognized in central regulation of appetite and food intake and possibly in other aspects of leptin action [45 ].…”
Section: Neurohormonal and Neuromodulators Of Breathingmentioning
confidence: 99%